2021
DOI: 10.4018/978-1-7998-7300-6.ch015
|View full text |Cite
|
Sign up to set email alerts
|

Marketing and Sponsorship of Esports Without Getting Ganked

Abstract: Sports sponsorship is an area of marketing responsible for raising financial resources. This is a similar understanding within the realm of Esports as the fastest growing sport in decades. Recognizing the clear parallel between sports and Esports within the marketing realm, as ways through which to raise financial resources through sponsorship opportunities, there are also significant differences that apply, partially due to the digital comfortability of gamers as a novel and as yet unexperienced curiosity, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Corporate image implies performing CSR to shape better image, changing the public's perception and identification, and enhancing the visibility and credibility, which highlights similar arguments reflected by a group of previous studies [9,13,[25][26][27][28][29][30]. On the other hand, marketing instrument focuses on enlarging market share, reaching the connection with target consumers, and maximizing sponsorship investment effectiveness, which also involves similar arguments indicated by other previous studies [31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Corporate image implies performing CSR to shape better image, changing the public's perception and identification, and enhancing the visibility and credibility, which highlights similar arguments reflected by a group of previous studies [9,13,[25][26][27][28][29][30]. On the other hand, marketing instrument focuses on enlarging market share, reaching the connection with target consumers, and maximizing sponsorship investment effectiveness, which also involves similar arguments indicated by other previous studies [31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 65%
“…For example, Su and Kunkel [32] analyzed that the enterprises with lesser-known brands can enlarge market share of products or services through effective sponsoring events in a competitive environment. Rosário and Raimundo [33] argued that launching sponsorship can reach the connection with target consumers, which is also proved by Premananto and Zulkifli [34] in exploring the performance of sponsorship events. Zhang [35] indicated that sponsorship-linked marketing is correlated with return on investment, helping corporations maximize sponsorship investment effectiveness.…”
Section: Marketing Instrument (Mi)mentioning
confidence: 69%
See 1 more Smart Citation